Numerical Solution of Newell-Whitehead-Segel Partial Differential Equation by Finite Difference Methods (Latakia University Journal -Basic Sciences Series, 2019)
This work presents two different finite difference methods, which are implicit finite difference method and fully implicit finite difference method to compute the numerical solutions for Newell-Whitehead-Segel partial differential equation. Newton's method is used in fully implicit finite difference scheme, because this scheme leads to a system of nonlinear equations. Two different problems are solved by the both previous proposed methods. The results show the accuracy of the numerical solution and its agreement with the exact solution.